Pengaruh Struktur Kepemilikan, Pelanggan dan Slack Organisasi Terhadap Pengungkapan Tanggungjawab Sosial Perusahaan (Studi Empiris Pada Perbankan Indonesia Yang Terdaftar di BEI Tahun 2013 – 2015) - Julia Julia (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
The purpose of this study was to test the effect of ownership structure, customer and organizational slack on the disclosure of corporate social responsibility in the annual report of the Indonesian banking sector in 2013 through 2015 are listed in the Indonesia Stock Exchange (BEI). This research is quantitative using simple random sampling method. The data used in this study secondary data, banking 2013-2015 annual report. Sources of data obtained through the website of the Stock Exchange data using eviews with OLS regression.The results of the study hypothesis for H1a, H1b, and H1c which influence the structure of ownership (concentrated ownership, government, and foreign) on the disclosure of corporate social responsibility, is accepted. As for the hypothesis H2 and H3 that influence customer and organizational slack on the disclosure of social responsibility, rejected. This study found that organizational slack regarded as costs by the company not as a source of additional power while the customer does not care about social responsibility then this may affect the disclosure of CSR in the banking sector.